AKUNTABILITAS PELAPORAN KEUANGAN DAN ASET DESA BERBASIS SHARIATE ENTERPRISE THEORY - Nikmatuniayah Nikmatuniayah; Resi Yudhaningsih; Lilis Mardiana (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2020)
This study aims to formulate a Model of Accountability in Financial Reporting and Village Assets based on Shariate Enterprise Theory. Specifically, this study aims to dissect the accountability factors of financial management and village assets based on: spiritual, ecological, economic and social. This research method uses the qualitative approach of Moleong (2005), which uses the pragmatic research method. The development of accountability models in this study uses Shariate Enterprise Theory. A qualitative approach is carried out by analyzing documents, observations, interviews, surveys and exploration. This research has identified indicators of accountability models for financial and asset management. Accountability in the process of determining this indicator will be divided into four dimensions, namely: the dimension of Accountability between humans and society; Human accountability to the state; Human accountability to nature; Human accountability with Allah.